Biomechanical alterations during gait following partial ACL injury and the effectiveness of anatomical reconstruction: an in–vitro robotic investigation - Lin, Jinpeng; Cheng, Rongshan; Yan, Yuan; Zeng, Xiaolong; Huang, Wenhan; Deng, Chunlin; Tsai, Tsung-Yuan; Wang, Shaobai; Zhang, Yu (Frontiers in Bioengineering and Biotechnology, 2025)
BackgroundThe biomechanical alterations of the knee throughout the gait cycle following partial anterior cruciate ligament (ACL) injuries remain unclear.PurposeThis study aimed to investigate the changes in intra-articular contact mechanics during gait following partial ACL injury and to evaluate whether anatomical single-bundle ACL reconstruction (ACLR) could restore these altered mechanics.MethodsSeven fresh-frozen cadaveric knee specimens were used to evaluate tibiofemoral joint biomechanics under three ligamentous conditions: intact ACL, anteromedial bundle deficiency (AMD), and single-bundle ACLR. A 6 degree of freedom (DOF) robotic system simulated gait motion using physiological loading conditions derived from human. Biomechanical parameters, including peak contact stress, displacement of contact center of stress (CCS), and regional loading patterns, were analyzed at five key gait cycle stages. Statistical analyses were performed using repeated-measures ANOVA and paired t-tests, with significance set at p < 0.05.ResultsAMD knees demonstrated a slight posterior shift in the CCS (<2 mm) during the stance phase, with significant increases in medial compartment regional loading at heel strike (4.11 ± 1.5 N, p = 0.04) and terminal stance (6.31 ± 1.35 N, p = 0.048). ACLR knees exhibited greater posterior CCS displacement in the lateral compartment at heel strike (2.73 ± 1.98 mm vs 0.21 ± 1.97 mm, p = 0.022). The sustained posterior shift in CCS will lead to abnormal loading at the posterior horn of the lateral meniscus, potentially accelerating meniscal tears or degeneration and increasing the incidence of lateral osteoarthritis. Additionally, ACLR knees exhibited significant force increases across both compartments, including the lateral compartment at terminal stance (11.91 ± 2.58 N, p = 0.027) and the medial compartment at pre-swing (11.72 ± 2.17 N, p = 0.011).ConclusionAnteromedial bundle injury alters medial compartment loading during gait, causing a slight posterior shift of the center of CCS. And that anatomical single-bundle ACLR does not fully replicate the native anterior cruciate ligament’s biomechanical function.